2011
DOI: 10.1109/jqe.2011.2107730
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Fiber Lasers to Large Mode Area: An Investigation of Passive Mode-Locking Using a Multi-Mode Fiber

Abstract: The mode-locking of dissipative soliton fiber lasers using large mode area fiber supporting multiple transverse modes is studied experimentally and theoretically. The averaged mode-locking dynamics in a multi-mode fiber are studied using a distributed model. The co-propagation of multiple transverse modes is governed by a system of coupled Ginzburg–Landau equations. Simulations show that stable and robust mode-locked pulses can be produced. However, the mode-locking can be destabilized by excessive higher-orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…Motivated by the successes in amplifiers, Ding and co-workers performed a study of normal-dispersion lasers constructed with multimode fiber. These workers found that lasers constructed with coiled multimode fiber consistently exhibit multi-pulsing at energies well below those achieved with the photonic-crystal fibers [44]. A simplified model of a laser with two transverse modes is consistent with the experimental observations.…”
Section: Scaling Power and Energy In Large-mode-area Fiberssupporting
confidence: 52%
“…Motivated by the successes in amplifiers, Ding and co-workers performed a study of normal-dispersion lasers constructed with multimode fiber. These workers found that lasers constructed with coiled multimode fiber consistently exhibit multi-pulsing at energies well below those achieved with the photonic-crystal fibers [44]. A simplified model of a laser with two transverse modes is consistent with the experimental observations.…”
Section: Scaling Power and Energy In Large-mode-area Fiberssupporting
confidence: 52%
“…[7]. The scaling factor of ~ 10 is consistent with the ratio of mode areas, confirming sufficient higher-order mode filtering for high-energy mode-locking [12] . From this controlled point, the cavity can be optimized for performance.…”
Section: Resultssupporting
confidence: 60%
“…This is achieved using fundamental-mode excitation and higher-order mode (HOM) suppression, usually through selective bend loss [10] . A modelocked soliton laser based on multimode fiber was demonstrated [11] , but suppressing HOMs to obtain stable modelocking at high single pulse energies remains a challenge [12] . Photonic crystal fibers and rods have enabled effectively single-mode lasers reaching megawatt peak powers [13], [14], [15] , but integrating these cavities into monolithic designs presents a serious challenge due to high bend sensitivity and incompatibility with standard fiber fusion technology.…”
Section: Introductionmentioning
confidence: 99%
“…The refractive index profile of a GIMF is given by (1) where is the core radius, is the maximum refractive index in the center of the core, is the relative index step, and characterizes a near parabolic-index profile. The transverse electric field of a propagating mode can be decomposed into separate radial and angular components as (2) where [12] (3)…”
Section: Brief Overview Of Gimfsmentioning
confidence: 99%
“…For example, there has been a surge of interest recently in multimodemultiplexed fiber-optic communications for ultrahigh-data-rate transmission [1]. Recently, a pioneering work on the integration of MMFs in mode-locked fiber lasers was reported; MMFs were used to reduce the total nonlinear phase shift in the fiber laser cavity in order to increase the pulse energy [2]. We also recently reported using graded-index multimode fibers (GIMFs) to build mode-field adapters and ultralow-loss couplers using the multimode interference (MMI) effect [3], [4].…”
Section: Introductionmentioning
confidence: 99%